COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF ISLAMIC COMMERCIAL BANKS DURING AND POST PANDEMIC IN INDONESIA - Masunah, Durrotul; Listiyowati, Listiyowati; Ambardi, Prio (Jurnal Asy-Syukriyyah, 2024)
Financing income at Islamic Banks during the Covid-19 pandemic in Indonesia decreased by 0.6%. It is due to consumer demand for restructuring. The net acquisition of Islamic returns also decreased significantly from 7.41% to 6.12% due to the pandemic. This research aims to determine whether there is a difference in the Financial Performance of Islamic Commercial Banks during and after the Covid-19 pandemic. The research method used is quantitative with the object of research at Islamic Commercial Banks. The researchers took samples through the purposive sampling method. The researchers also used descriptive statistical analysis and hypothesis testing using the paired sample t-test. In the test, the researchers used SPSS 25. The research results indicate that there is no significant difference in the financial performance of Islamic Commercial Banks during and after the Covid-19 pandemic with a calculated t value < t table of 0.320 < 2.265 with a significance of 0.756 > 0.05 in the liquidity ratio, with a calculated t value < t table of -0.574 < 2.265 with a significance of 0.580 > 0.05 in the profitability ratio, with a calculated t value < t table of 0.524 < 2.265 with a significance of 0.613 > 0.05 in the solvency ratio, with a calculated t value < t table of 1.410 < 2.265 with a significance of 0.192 > 0.05 in the business efficiency ratio, with a calculated t value < t table of 1.444 < 2.265 with a significance of 0.183 > 0.05 on leverage ratio.